Evaluation of Diagnostic Methods for Asymptomatic Bacteriuria (ASB) During Pregnancy: Life Sciences-Medicine - Abdelaal, Reem Anwar; Mohammed Ibrahim, Ghalia; Baraka, Ali Hashim; Hamed Mohammed, Islam; Hassan Ali, Nuha; Yousif Abdelrahman, Rayyan; Abdelbasit, Hadia Babiker; Abdelghani, Sara; Bashier Eltayeb, Lienda (International Journal of Life Science and Pharma Research, 2022)
Asymptomatic bacteriuria (ASB) is the existence of bacteria in a patient's properly gathered urine who has no obvious symptoms of a urinary tract infection, which is common in females, with the prevalence rate of 2-11%, ASB during pregnancy is influenced by a range of factors including; mechanical compression, changes in the immune and renal systems, if ASB untreated, it can lead to cystitis and pyelonephritis. Our aim is to evaluate the sensitivity and specificity of the screening tests compared with the culture method for detection of ASB during pregnancy, and to identify the most common etiologic agents of ASB in pregnant women. An analytical cross- sectional study was carried out on 110 pregnant women, selected using nonprobability sampling methods their age between 18-45year- old with no signs and symptoms of urinary tract infections (UTIs). Clean-catch Midstream urine specimen from each participant was collected and submitted for routine analysis by dipstick to detect leukocyte esterase, nitrite reductase tests and microscopic examination to detect pyuria (pus cells), as well as urine culture, and biochemical test. About 14.5% of pregnant women were positive for ASB, the most prevalent bacterium Escherichia coli (37.5%) followed by Klebsiella pneumoniae (18.7%). There was no significant association between age, parity, gestation, recurrent urinary tract infections, Diabetes mellitus, hypertension and ASB. For screening tests; the nitrite test was more specific (98.9%) than leukocyte esterase and pus cells, on the other hand, pus cell detection was more sensitive (81.2%) than the other tests for detection of ASB. The prevalence of ASB was relatively high, no one used routine screening tests revealed both high sensitivity and specificity. So, urine culture remains the gold standard method for detection of ASB in pregnant women.